Strategic managerial solutions for innovations in agrifood industry - Garnyk, Liudmyla Petrivna; Vitkovskyi, Y. P.; Sherstyuk, Valeriy (Association-Institute of English Language and American Studies, 2020)
Purpose of the paper is caused by sophisticated and controversial situation that has being occurred in Ukrainian Agrifood industry since beginning of 21st century. Development of Agrifood industry and especially its export potential were defined as strategic targets of national economics, but it is impossible to gain such goals without strategic managerial solutions for innovations in this area (see figure 1). Nowadays sustainable development of Agrifood industry depends on constellation of factors with different nature of origin that requires toolkit of instruments based on Quality management philosophy and validated analytical models. Research methodology is based on five pillars of systematic innovations philosophy as conceptual framework for constructing flexible and competitive business models based on excellence logics that was transformed into comprehensive Systematic Innovation methodology applicable for all types of innovations and relevant management issues. Chosen research approach helped us to adopt mentioned above methodology for economic reality of Ukraine as like as other post-soviet union or post-colonial national economic systems in transition. Results of our research are algorithms that allow systematically and reliably find out innovative managerial solutions to increase export potential of national Agrifood industry based on quality management philosophy and strategic risk management agenda, aimed on getting synergy effects from partnership between different stakeholders. Research and practical implications of the research implemented into analytical instruments that allow to evaluate innovative potential of Agrifood industry entity and its responsibility to attract needed resources to develop, adopt and implement innovations on practice.
Keywords: strategic managerial solutions; innovations; Agrifood industry; philosophy of quality management; export potential